ChemInform Abstract: Superacid Synthesized Tertiary Benzenesulfonamides and Benzofuzed Sultams Act as Selective hCA IX Inhibitors: Toward Understanding a New Mode of Inhibition by Tertiary Sulfonamides. Issue 12 (25th March 2014) - Metayer, Benoit; Martin‐Mingot, Agnes; Vullo, Daniella; Supuran, Claudiu T.; Thibaudeau, Sebastien
Abstract A series of tertiary, fluorinated benzenesulfamides (II) is synthesized in superacid HSbF6.